Bearing Steel Technologies : 12th Volume, Progress in Bearing Steel Metallurgical Testing and Quality Assurance - Beswick, John M. (ASTM International, 2020)
THIS COMPILATION OF Selected Technical Papers, STP1623, Bearing Steel Technologies: 12th Volume, Progress in Bearing Steel Metallurgical Testing and Quality Assurance, contains peer-reviewed papers that were presented at a symposium held May 15-17, 2019, in Denver, CO, USA. The symposium was jointly sponsored by ASTM International Committee A01 on Steel, Stainless Steel and Related Alloys, and Subcommittee A01.28 on Bearing and Power Transmission Steels.
ASTM Stock Number: STP1623.
Keywords: Steel, Bearing.; Steel, Bearing -- Fatigue.; elektronické knihy; electronic books